DESAIN MODUL PEMBELAJARAN BERBASIS KEMAMPUAN KOMUNIKASI MATEMATIS DAN MOTIVASI BELAJAR SISWA - Sofi Saifiyah; Ferry Ferdianto; Setiyani Setiyani (KALAMATIKA Jurnal Pendidikan Matematika, 2017)
This research about an instructional module design for mathematical communication skills and student motivation. This type of research is descriptive qualitative research in the form of a didactic design. Research background by the barriers to learning (learning obstacle) experienced by students regarding the material rectangle and related mathematical communication skills in junior high school students of class VII. One solution to overcome learning obstacles experienced by students is designing learning modules in order to facilitate the students to understand the material rectangular and square and encourage mathematical communication skills. The study aims to: (1) know learning obstacles experienced by students; (2) knowing how to design a learning module that is valid in accordance with learning obstacles experienced by students; (3) describe the intervention of teachers in implementing the learning modules; and (4) determine students' motivation after learning using learning modules. His research interests are students of class VII C SMP Negeri 1 palimanan. The results of this study indicate the existence of two kinds of learning obstacles experienced by students, the learning module valid after being revised in accordance with the advice of the fifth validator validation learning modules percentage reached 86.80% with a very valid criteria or can be used without revision, intervention by teachers during the implementation of the learning modules in the form of anticipation of didactic and pedagogical intervention, and the average student motivation after learning to use the learning module reaches 83.78% which is included in the category of a very strong motivation to learn.